Repair of articular cartilage defects with acellular cartilage sheets in a swine model. (1st February 2018) - Xue, Jixin; He, Aijuan; Zhu, Yueqian; Liu, Yu; Li, Dan; Yin, Zongqi; Zhang, Wenjie; Liu, Wei; Cao, Yilin; Zhou, Guangdong
Abstract: Acellular cartilage sheets (ACSs) have been demonstrated as a good biomaterial for cartilage regeneration as a result of their natural cartilage matrix components, cartilage-specific structures, and good biocompatibility. However, it remains unknown whether allogeneic ACSs could promote cartilage regeneration and repair cartilage defects in a large animal model. The current study explored the feasibility of repairing articular cartilage defects using ACS scaffold with or without autologous bone marrow stromal cells (BMSCs) in a swine model. According to the current results, ACSs retained natural cartilage structure, primary cartilage matrices, and cartilage-specific growth factors. After cell seeding, ACSs presented good biocompatibility with BMSCs, which produced abundant extracellular matrix (ECM) proteins to cover the lacuna structures. In vivo results indicated that ACSs alone could induce endogenous host cells to regenerate cartilage and achieve generally satisfactory repair of cartilage defects at 6 months post-operation, including good interface integration and cartilage-specific ECM deposition. After combination with autologous BMSCs, BMSC-ACS constructs achieved more satisfactory repair of cartilage defects even without in vitro pre-induction of chondrogenesis. More importantly, all defects in both BMSC-ACS and ACS-only groups showed enhanced cartilage regeneration compared with BMSC–polyglycolic acid and blank groups, which mainly exhibited fibrogenesis in defect areas. Collectively, the current results indicate that ACSs can efficiently repair articular cartilage defects by promoting chondrogenic differentiation of BMSCs or inducing endogenous chondrogenesis in situ, thus serving as a good cartilage regeneration scaffold for recovery of articular function.